1998
DOI: 10.1071/am98299
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of The Habitat Characteristics of Pools Used by Platypuses (Ornithorhynchus Anatinus) in the Upper Macquarie River System, New South Wales.

Abstract: The study conducted during 1993 assessed the habitat characteristics of 36 pools along the upper Macquarie River system. A range of biophysical parameters were assessed at each site, including: pool morphology; riparian floristics and habitat structure; benthic substrate composition; and physicochemical properties. The results of a complementary observation program indicated that 19 of the pools were being used by platypuses. Statistical analyses were carried out to identify significant platypus-habitat relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…These are normally dug into earth which is consolidated by the roots of riparian vegetation. The presence of riparian vegetation overhanging river banks has been identi¢ed in all three studies as an important habitat requirement of the platypus (Rohweder 1992;Bryant 1993;Woon 1995;Ellem et al 1998). This is probably due to the shelter provided for individuals foraging in the stream near the bank and permitting safe access to burrow entrances.…”
Section: Habitat Requirementsmentioning
confidence: 99%
See 4 more Smart Citations
“…These are normally dug into earth which is consolidated by the roots of riparian vegetation. The presence of riparian vegetation overhanging river banks has been identi¢ed in all three studies as an important habitat requirement of the platypus (Rohweder 1992;Bryant 1993;Woon 1995;Ellem et al 1998). This is probably due to the shelter provided for individuals foraging in the stream near the bank and permitting safe access to burrow entrances.…”
Section: Habitat Requirementsmentioning
confidence: 99%
“…A number of workers have used visual observations to assess presence or absence of the species in an area. The numbers of individuals observed at one time can be used as a measure of broad categories of abundance, such as rare',`common' or`abundant' (Grant 1992b;Rohweder 1992;Bryant 1993;Woon 1995). However, observations and netting together show that lack of observation may not necessarily indicate absence of the species from an area because platypuses have been captured at locations where local people have indicated that the species is absent (T. R. Grant, unpublished data).…”
Section: Abundancementioning
confidence: 99%
See 3 more Smart Citations